New Frontier in Glycoprotein Hormones and Their Receptors Structure–Function - Szkudlinski, Mariusz W. (Frontiers in Endocrinology, 2015)
Last two decades of structure-function studies performed in numerous laboratories provided substantial progress in understanding basic science, physiological, pathophysiological, pharmacological and comparative aspects of glycoprotein hormones (GPHs) and their cognate receptors. Multiple concepts and models developed based on experimental data in the past stood the test of time and have been, at least in part, confirmed and/or remained compatible with the new structures resolved at the atomic level. Major advances in understanding of the ligand-receptor relationships are heralding the dawn of a new era for GPHs and their receptors (GPHRs), although many basic questions still remain unanswered. This article examines retrospectively several basic science aspects of GPH super- agonists and related “biosuperiors” in a broader context of the advances in the ligand-receptor structure-function relationships and new mechanistic models generated based on the structure elucidation. Due to selective focus of my comments and perspectives in certain parts the reader is directed to the most relevant publications and reviews in the field for more comprehensive analyses.